HIGH-FREQUENCY SURFACE CURRENTS INDUCED ON A SOFT-HARD CYLINDRICAL STRIP - GOKSU, C; GUNES, F (IEE-INST ELEC ENG, 1991)
The high frequency surface currents induced on a soft-hard cylindrical strip because of the infinite successive diffraction are investigated. The problem is treated in the extended angular space. The resulting mixed boundary problem is converted to a modified matrix Hilbert-Wiener Hopf problem and reduced to a coupled integral equation for high frequencies and solved. The currents are shown to represent the infinite successive diffraction of the dominant term, created by the surface and first edge diffraction.
Keywords: ELECTROMAGNETIC THEORY; SURFACE CURRENTS; Engineering